Modification of Chitosan using Fe3O4 and Glucose and Its Application for Phenol Removal - Rizki, Widya Twiny; Lestari, Siti Marwah; Rahmah, Vindi Annisa; Dauli, Rd Rahmat (Universitas Gadjah Mada, 2025)
In this study, chitosan was modified with Fe3O4 and glucose to enhance its capacity and effectiveness in adsorbing phenol from organic waste. XRD analysis revealed distinct differences between unmodified chitosan and the Fe3O4/glucose-modified version, with the resulting nanocomposite showing a particle size of 17.21 nm. FTIR spectra exhibited new, sharper peaks at 531 and 544 cm−1, indicating interactions between chitosan and Fe3O4 via the nitrogen atom in the NH2 group. VSM characterization showed a saturation magnetization of 63.4 emu/g, confirming that the chitosan/Fe3O4/glucose nanocomposite is superparamagnetic. SEM analysis revealed an uneven, porous surface, while the morphology displayed dark Fe3O4 spots dispersed across a lighter chitosan matrix. The optimal adsorption condition was achieved at a contact time of 60 min, with an adsorption efficiency of 16.46%. In addition to reducing phenol content in wastewater, the modified nanocomposite also exhibited antibacterial activity against Staphylococcus aureus and Escherichia coli. This multifunctional material offers a promising solution for wastewater treatment, targeting both organic pollutants and pathogenic bacteria to help address water pollution challenges.